miR-103a-3p and miR-22-5p Are Reliable Reference Genes in Extracellular Vesicles From Cartilage, Adipose Tissue, and Bone Marrow Cells - Ragni, Enrico; Colombini, Alessandra; De Luca, Paola; Libonati, Francesca; Viganò, Marco; Perucca Orfei, Carlotta; Zagra, Luigi; de Girolamo, Laura (Frontiers in Bioengineering and Biotechnology, 2021)
Cartilage cells (CCs), adipose tissue (ASCs)- and bone marrow (BMSCs)-derived mesenchymal stromal cells (MSCs) have been shown as promising candidates for the conservative treatment of osteoarthritis (OA). Despite their adaptive ability, the exposure to chronic catabolic and inflammatory processes can limit their survival and healing potential. An attractive cell-free alternative or complementary strategy is represented by their secreted extracellular vesicles (EVs), which showed homeostatic properties on OA chondrocytes and synovial cells. In view of clinical translation, a thorough characterization of the shuttled therapeutic molecules, as miRNAs, is greatly needed to fingerprint and develop the most effective EV formulation for the OA treatment. To date, a crucial pitfall is given by the lack of EV-miRNA associated reference genes (RGs) for the reliable quantification and comparison among different therapeutic EV-based therapeutic products. In this study, the stability of 12 putative miRNA RGs (let-7a-5p, miR-16-5p, miR-22-5p, miR-23a-3p, miR-26a-5p, miR-29a-5p, miR-101-3p, miR-103a-3p, miR-221-3p, miR-423-5p, miR-425-5p and miR-660-5p), already proposed by literature in EV products from alternative sources, was assessed in EVs isolated from three donor-matched ASCs, BMSCs and CCs through geNorm, NormFinder, BestKeeper and ΔCt algorithms, and the geometric mean of rankings. ASC-EVs and BMSC-EVs shared more similar molecular signatures than cartilage-derived EVs, although overall miR-103a-3p consistently ranked as the first and miR-22-5p as the second most stable EV-miRNA RG, whereas miR-221-3p behaved poorly. Further, to emphasize the impact of incorrect RG choice, the abundance of four OA-therapeutic miRNAs (miR-93-5p, miR-125b-5p, miR-455-3p and miR-27b-3p) was compared. The use of miR-221-3p did not allow a correct quantification of miRNA incorporation in EVs, leading to less accurate fingerprinting and, when applied to sift therapeutic potency prediction, misleading indication of the most appropriate clinical product. In conclusion, miR-103a-3p and miR-22-5p will represent reliable RGs for the quantification of miRNAs embedded in MSC- and CC-EVs, a mandatory step for the molecular definition and comparison of the clinical potency of these innovative cell-free based therapeutic products for OA in particular, and for a wider array of regenerative-medicine based approaches.